English-Swedish-Turkish Corpus - Megyesi, Beáta; Csató Johanson, Éva; Dahlqvist, Bengt; Nivre, Joakim; Pettersson, Eva (Uppsala University, 2020)
We describe a syntactically annotated parallel corpus containing typologically partly different languages, namely English, Swedish andTurkish. The corpus consists of approximately 300 000 tokens in Swedish, 160 000 in Turkish and 150 000 in English, containing bothfiction and technical documents. We build the corpus by using the Uplug toolkit for automatic structural markup, such as tokenizationand sentence segmentation, as well as sentence and word alignment. In addition, we use basic language resource kits for the linguisticanalysis of the languages involved. The annotation is carried on various layers from morphological and part of speech analysis todependency structures. The tools used for linguistic annotation, e.g., HunPos tagger and MaltParser, are freely available data-drivenresources, trained on existing corpora and treebanks for each language. The parallel treebank is used in teaching and linguistic researchto study the relationship between the structurally different languages. In order to study the treebank, several tools have been developedfor the visualization of the annotation and alignment, allowing search for linguistic patterns.

Purpose:

The main goal of the project is to promote research and teaching in the Turkish language. More specifically, the aim is to build a language resource for Turkish, Swedish and English allowing contrastive studies between the involved languages.

We describe a syntactically annotated parallel corpus containing typologically partly different languages, namely English, Swedish andTurkish. The corpus consists of approximately 300 000 tokens in Swedish, 160 000 in Turkish and 150 000 in English, containing bothfiction and technical documents. We build the corpus by using the Uplug toolkit for automatic structural markup, such as tokenizationand sentence segmentation, as well as sentence and word alignment. In addition, we use basic language resource kits for the linguisticanalysis of the languages involved. The annotation is carried on various layers from morphological and part of speech analysis todependency structures. The tools used for linguistic annotation, e.g., HunPos tagger and MaltParser, are freely available data-drivenresources, trained on existing corpora and treebanks for each language. The parallel treebank is used in teaching and linguistic researchto study the relationship between the structurally different languages. In order to study the treebank, several tools have been developedfor the visualization of the annotation and alignment, allowing search for linguistic patterns.

Syfte:

Det övergripande syftet med projektet är att främja forskning och undervisning i turkiska. Mer specifikt syftar projektet till att bygga upp språkteknologiska basresurser för turkiska, svenska och engelska med kontrastiva frågeställningar i fokus.
Engelsk-svensk-turkisk korpus
Keywords: linguistics; lingvistik; texts; texter; Language and linguistics; Språk och lingvistik; Languages and Literature; Språk och litteratur